Oxidation of Phospholipids by OH Radical Coordinated to Copper Amyloid-β Peptide—A Density Functional Theory Modeling - Alberto Rovetta; Laura Carosella; Federica Arrigoni; Jacopo Vertemara; Luca De Gioia; Giuseppe Zampella; Luca Bertini (Inorganics, 2023)
Oxidative stress and metal dyshomeostasis are considered crucial factors in the pathogenesis of Alzheimer’s disease (AD). Indeed, transition metal ions such as Cu(II) can generate reactive oxygen species (ROS) via O2 Fenton-like reduction, catalyzed by Cu(II) coordinated to the amyloid-beta (Aβ) peptide. Despite intensive efforts, the mechanisms of ROS-induced molecular damage remain poorly understood. In the present paper, we investigate, on the basis of Density Functional Theory (DFT) computations, a possible mechanism of the OH radical propagation toward membrane phospholipid polar head and fatty acid chains starting from the end-product of the OH radical generation by Cu(II)-Aβ. Using phosphatidylcholine as a model of a single unit inside a membrane, we evaluated the thermochemistry of the OH propagation with the oxidation of a C-H bond and the formation of the radical moiety. The DFT results show that Cu(II)-Aβ-OH can oxidize only sn-2 C-H bonds of the polar head and can easily oxidize the C-H bond adjacent to the carbon–carbon double bond in a mono or bis unsaturated fatty acid chain. These results are discussed on the basis of the recent literature on in vitro Aβ metal-catalyzed oxidation and on the possible implications in the AD oxidative stress mechanism.